Outcomes for patients with second primary malignancy after primary surgical treatment for early‐stage squamous cell carcinoma of the oral cavity. Issue 11 (10th October 2018) - Suton, Petar; Prpic, Marin; Tarle, Marko; Mamic, Matija; Nikles, Iva; Luksic, Ivica
Abstract: Background: The purpose of our article was to describe a tertiary center's experience with patients with primarily surgically treated early‐stage intraoral cancer with a second primary malignancy confirmed during follow‐up. Methods: A total of 183 patients were primarily surgically treated for oral cancer between 2000 and 2004. Among these, 24 patients (13.1% (24/183)) met inclusion criteria. Results: There were 22 men (91.7%) and 2 women (8.3%) with a median age of 59.5 years. Patients with head and neck cancer with a second primary malignancy had significantly higher survival compared to nonhead and neck cancer with a second primary malignancy. Patients with head and neck cancer with second primary malignancy were diagnosed during the period of 14 to 45 months (median 29 months), whereas nonhead and neck cancer with second primary malignancy occurred in a period of 7 to 46 months (median 19 months). Conclusion: This study highlights the importance of optimizing screening strategies for second primary malignancies. In order to improve the survival of patients with head and neck squamous cell carcinoma (HNSCC), effective programs of screening and/or chemoprevention of second primary malignancies are essential.